2012
DOI: 10.1155/2012/965953
|View full text |Cite
|
Sign up to set email alerts
|

Role of TGF-β1/Smad3 Signaling Pathway in Secretion of Type I and III Collagen by Vascular Smooth Muscle Cells of Rats Undergoing Balloon Injury

Abstract: Antisense Smad3 adenoviral vectors were used to transfect vascular smooth muscle cells (VSMCs) from rats with balloon injury or infused into the rat balloon-catheter injured carotid arteries, and the role of TGF-β1/Smad3 signaling pathway in the secretion of type I and III collagen by VSMCs following balloon injury was investigated. Antisense Smad3 adenoviral vectors were used to transfect these VSMCs (antisense Smad3 group). A total 90 rats were randomly assigned into blank control group, experiment group, ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…Phosphorylation of Smad3 by active TGF‐βRI leads to complex formation with Smad4, followed by nuclear translocation [Shi and Massague, ; Massague, ]. After releasing from the complex, Smad3 binds to the promoter, associates with other transcription factors, and initiates the transcription of target genes [Das et al, ; Lu et al, ]. Our results illustrated that both 3A‐FoxO1 and SiRNA‐FoxO1 did not affect Smad3 expression levels, whereas high‐glucose‐induced elevation of p‐Smad3 protein was decreased after overexpression of 3A‐FoxO1.…”
Section: Discussionmentioning
confidence: 66%
“…Phosphorylation of Smad3 by active TGF‐βRI leads to complex formation with Smad4, followed by nuclear translocation [Shi and Massague, ; Massague, ]. After releasing from the complex, Smad3 binds to the promoter, associates with other transcription factors, and initiates the transcription of target genes [Das et al, ; Lu et al, ]. Our results illustrated that both 3A‐FoxO1 and SiRNA‐FoxO1 did not affect Smad3 expression levels, whereas high‐glucose‐induced elevation of p‐Smad3 protein was decreased after overexpression of 3A‐FoxO1.…”
Section: Discussionmentioning
confidence: 66%
“…A class of anti-stimulus signalling cascades would then be triggered, accompanied with cellular functions, such as proliferation, apoptosis, differentiation and migration, are regulated. One DE gene of Smad3 (28)(29)(30)(31) in our study (Table S2), is an important component of the TGF-b signalling pathway, regulating a wide spectrum of cellular functions. Matsubara et al (31) concluded that the TGF-b-Smad3 signalling pathway mediates hepatic bile acid and phospholipid metabolism following lithocholic acid-induced liver injury.…”
Section: Discussionmentioning
confidence: 88%
“…A class of anti‐stimulus signalling cascades would then be triggered, accompanied with cellular functions, such as proliferation, apoptosis, differentiation and migration, are regulated. One DE gene of Smad3 in our study (Table S2), is an important component of the TGF‐β signalling pathway, regulating a wide spectrum of cellular functions. Matsubara et al .…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, resident neointimal SMCs and stellate cells will enhance neointimal collagen content. Therefore, neointimal fibroblast and myofibroblast may be crucial in type III collagen synthesis, leading to neointimal expansion [23,24]. These cells were extensively studied previously in coronary artery restenosis [2529].…”
Section: Introductionmentioning
confidence: 99%